Nearly Half of Women Have Experienced Intimate Partner Violence During Pregnancy in Northwest Ethiopia, 2021; The Role of Social Support and Decision-Making Power - Kebede, Azmeraw Ambachew; Aklil, Mastewal Belayneh; Gessesse, Dereje Nibret; Tsega, Nuhamin Tesfa; Temesgan, Wubedle Zelalem; Abegaz, Marta Yimam; Anteneh, Tazeb Alemu; Tibebu, Nebiyu Solomon; Alemu, Haymanot Nigatu; Haile, Tsion Tadesse; Seyoum, Asmra Tesfahun; Tiguh, Agumas Eskezia; et al. (Frontiers in Public Health, 2022)
Background: In developing countries, intimate partner violence is increasing alarmingly, though attention to this issue is rarely given. It has devastating effects on the general well-being of women, pregnancy outcomes, and the long-term health of children, and this needs to be addressed. Hence, this study was designed to assess intimate partner violence and associated factors in northwest Ethiopia. Methods: A community-based cross-sectional study was conducted from July 1st to August 30th, 2021, among 858 postpartum women in Gondar city. A cluster sampling technique was employed to select the study participants. EPI DATA version 4.6 and SPSS 25 were used for data entry, cleaning and analysis, respectively. A bivariable and multivariable logistic regression model was fitted to identify factors associated with intimate partner violence. The level of significant association was declared using the adjusted odds ratio (AOR) with 95 % confidence interval (CI) and a p-value of ≤ 0.05. Results: In this study, 48.6% of women indicated having experienced intimate partner violence during pregnancy (95% CI: 45.3, 51.7). The odds of intimate partner violence during pregnancy were significantly higher among women who were not able to read and write (AOR = 4.96; 95% CI: 2.15, 11.41), were private workers (AOR = 1.78; 95% CI: 1.05, 3.02), and had low decision-making power (AOR = 1.43; 95% CI: 1.06, 1.95), a poor social support (AOR = 1.99; 95% CI: 1.32, 3.02), and unsupported pregnancy by family (AOR = 2.32; 95% CI: 1.26, 4.24). Whereas a family size of ≥ 5 (AOR = 0.73; 95% CI: 0.54, 0.98) appeared to be a protective factor for intimate partner violence. Conclusion: The magnitude of intimate partner violence was unacceptably high in the study area and connected to poor women’s empowerment and social determinants of health. Thus, it is important to focus on interventions that improve women’s access to social support and allow them to participate in all aspects of household decision-making through community-based structures and networks. It is also important to encourage women to improve their educational status and arrange risk-free employment opportunities.